FORMATION AND DEVELOPMENT OF AN ECONOMIC MECHANISM FOR MANAGING LAND RESOURCES IN THE CONTEXT OF DIGITALIZATION OF AGRICULTURE - Alla GORDOPOLOVA; Evgeniy ZAVOROTIN; Nataliya TIURINA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of paper consists in developing the economic mechanism for increase in effective management of land resources in agriculture. Theoretical provisions of institutionalism, management, system approach, the general scientific and special methods were used in the course of the research. Considering influence of negative externalities on the market of the agricultural land and a deviation of the prices from equilibrium level, it is expedient to influence a market turnover of agricultural grounds by means of the priority directions of development: reductions of transactional costs for execution of transactions and registration of the property rights to the land plots, updating of cadastral cost of the land plots, accelerations of differentiation of the lands which are in federal, regional, regional property, etc. As a result of a research authors constructed the regional economic mechanism of management of land resources in agriculture on the basis of use of digital technologies. Thus, the mechanism includes the executive power, scientific centers, higher educational institutions, software products providing accumulation, updating, structuring, storage of cartographic and thematic information for adoption of optimal management decisions. The offered economic mechanism is recommended to be used when developing state programs.